2015
DOI: 10.1016/j.jval.2015.09.2835
|View full text |Cite
|
Sign up to set email alerts
|

Health Status and Quality of Life Among Nurses

Abstract: A739 adhered to, transparency issues remain. In contrast, clinical-effectiveness guidance is vague and compliance is very low which appears to be currently unrecognised as an issue. Therefore, a more stringent approach is needed when assessing PRO data within HTA, to ensure accurate measurement of treatment effectiveness to inform better decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These could directly or indirectly affect the overall health status and well‐being of nurses, thereby affecting the quality of services they render to patients. Several studies have supported the relationship between optimum health and quality of life (QOL; Horváthné Kívés et al., ; Zubaran, Persch, Tarso, Ioppi, & Mezzich, ). For instance, nurses who evaluated themselves as having poor health conditions also reported lower QOL than nurses who were healthier (Horváthné Kívés et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These could directly or indirectly affect the overall health status and well‐being of nurses, thereby affecting the quality of services they render to patients. Several studies have supported the relationship between optimum health and quality of life (QOL; Horváthné Kívés et al., ; Zubaran, Persch, Tarso, Ioppi, & Mezzich, ). For instance, nurses who evaluated themselves as having poor health conditions also reported lower QOL than nurses who were healthier (Horváthné Kívés et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have supported the relationship between optimum health and quality of life (QOL; Horváthné Kívés et al., ; Zubaran, Persch, Tarso, Ioppi, & Mezzich, ). For instance, nurses who evaluated themselves as having poor health conditions also reported lower QOL than nurses who were healthier (Horváthné Kívés et al., ). As QOL may reflect one's health and well‐being, QOL among nurses and its influencing factors must be assessed to ensure that they are in optimum health condition when attending to patients.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that nurses who considered their health as bad had a lower HRQoL (8). The quality of life is a broader concept than health and encompasses different physical, psychological, cultural, and social aspects of health and HRQoL improvement is one of the most important goals of healthcare systems (9,10).…”
Section: Introductionmentioning
confidence: 99%